CONCEPTUAL STUDY OF CHARAKOKTA PRADNYAPARADHA (INTELLECTUAL ERROR) AND ITS SIGNIFICANCE IN SHARIRA KRIYA (PHYSIOLOGY) - Akshay Pathak (International Journal of Ayurveda and Pharma Research, 2020)
Atma, Mana, Indriya and Indriyartha are involved in perception of knowledge. One of the three important causative factors of diseases is Pradnyaparadha i.e., Dhi-Dhriti-Smriti Vibhramsha (intellectual error). Pradnyaparadha is the main causative factor of many Nija (innate) diseases and all Agantu (accidental) diseases as well as Janapadodhvansa vyadhi (Epidemic diseases). Rationale: It becomes need of an hour to study the concept of Pradnyaparadha (intellectual error), one of the major causes of physical and mental diseases, in various dimensions. Objective: This is an attempt to study the concept of Pradnyaparadha as explained in Charaka Samhita and its significance in Sharir Kriya which gives a detailed account of Atma, Mana and Indriya. Results: The concept of Pradnyaparadha has been discussed at various places in Charaka Samhita. If one can avoid this intellectual error by following code of conduct as prescribed in Ayurveda and in various philosophical treatises, he or she will remain healthy and thus will be capable in achievement of goals of life. Conclusion: Wrongly perception of knowledge through combined effects of Atma, Mana, Indriya and Indriyartha is nothing but Pradnyaparadha. Avoidance of etiological factor i.e., avoidance of Pradnyaparadha (Intellectual error- Doing improper things knowingly) is the only preventive and curative measure for most of the diseases.